Sistem Informasi Pemesanan Jasa Fotografi pada Lights Photography - Rizal Sofyan; Arie Kusumawati (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
Lights Photography is one of the businesses that offers services to capture certain moments in the form of photos in Jakarta. The number of other competitors makes it a challenge for Lights Photography to further improve service for customers. Currently, to place an order still uses the direct arrival method and through the Official Line. With this method, customers do not get information directly, must communicate first. Therefore, this research aims to build an Order Information System on Lights Photography to place an order using the Web, and there is a variety of information that is useful for customers and helps internal storage of ordering data using the Prototyping development method. System design with Unified Modeling Language (UML), programming using the Laravel Framework, and database using MySQL. For system testing using Black-box testing.